Natural composites: polymeric matrices based on vegetable resources - Aranguren, Mirta Ines (2006)
The aim of this work has been to develop new composites using filler and resins obtained from renewable resources, combining low cost and good mechanical properties. The raw materials selected for the polymeric matrix were tannin extracts and plant oils. The tannin extracts are potential substitutes for phenol-formaldehyde wood-bonding adhesives and the vegetable oils can be functionalized to obtain unsaturated polyester resins to be further used in polymeric matrix formulations. Tannin and oil based composites using pine woodflour as filler were prepared and mechanically tested. The effect of the humidity on the mechanical properties was also evaluated.